Relationship between the inductive or deductive approach to case-based learning on academic performance, self-efficacy, and satisfaction of social work students - Méndez López, Fátima; Camarero-Grados, Loreto; Moleras-Serra, Anna; Heah, Rachel; Porroche Escudero, Ana; Sánchez-Arizcuren, Rafael (Acciones e Investigaciones Sociales, 2023)
Introduction: Case-Based Learning (CBL) teaching methodology is an active learning methodology that generates a higher level of student participation and significant learning. The aim of this study was to analyse and compare a CBL activity using deductive reasoning (analyse and extract theoretical concepts in a case provided for this purpose) and a CBL activity using inductive reasoning (create a case by implicitly introducing theoretical concepts) in terms of academic performance and student satisfaction, as well as to analyse the relationship of the latter with the perception of self-efficacy. Methodology: A descriptive cross-sectional study was developed. 111 students performed both CBL activities (deductive and inductive). Each learning activity dealt with theoretical contents of group psychology. The variables collected were: activity grade, satisfaction with each activity, theoretical exam grade and perception of self-efficacy. A descriptive, correlational, and comparative analysis was conducted using T-Student of related samples. Results: The grades for the inductive CBL activity were significantly higher than those for the deductive CBL activity (p=0.042). The students´ level of satisfaction in the item “helps to think critically” was evaluated more favourably for the deductive CBL activity (p=0.029). The relationship between the grade of the inductive CBL activity and that obtained in the theoretical exam was significant. There was no correlation between any of the activities and the perceived self-efficacy of the students. Conclusions: The CBL activity with inductive reasoning is more effective to achieve academic performance and the satisfaction with the activities evaluated by the students is high.